Diverse Activation Modes in the Hydroboration of Aldehydes and Ketones with Germanium, Tin, and Lead Lewis Pairs. (2nd December 2016) - Schneider, Julia; Sindlinger, Christian P.; Freitag, Sarah M.; Schubert, Hartmut; Wesemann, Lars
Abstract: Intramolecular germylene, stannylene, and plumbylene Lewis pairs were reacted with hexanal and yielded the cyclic addition products only with the germanium and tin reagents. In further reactivity studies, the hydroboration of aldehydes and ketones catalyzed by intramolecular germylene, stannylene, and plumbylene Lewis pairs was studied. In the case of the cyclic germylene Lewis pair, the product of the oxidative addition of pinacolborane at the germylene moiety was observed. According to stoichiometric as well as catalytic experiments, the intramolecular germylene Lewis pair acts as a catalyst in the hydroboration of aldehydes and ketones. The homologous stannylene Lewis pair forms a reactive tin hydride during the catalysis, which can also act as a catalyst in this transformation. Abstract : Unterschiedliche Reaktivität : Intramolekulare Germylen‐, Stannylen‐ und Plumbylen‐Lewis‐Paare wurden mit Hexanal umgesetzt, aber nur die Germanium‐ und Zinn‐Reagentien lieferten die cyclischen Additionsprodukte. Zudem wurde die katalytische Aktivität dieser intramolekularen Lewis‐Paare in der Hydroborierung von Aldehyden und Ketonen untersucht.